Neutral point inverter controller using H infinity techniques - M. Alsharif, Ali Omar (2014)
For applications in renewable energy and distributed generation, there is often a need to have a neutral line to provide a current path. This can be achieved by using a neutral-point circuit that consists of a conventional neutral leg and a split dc link. In this project, a H infinity (H∞ ) current controller is proposed to force the current flowing through the split dc link to be nearly zero so that the neutral-point current is stable, and then, a current control loop is added to eliminate the imbalance of the current so that the neutral-point current is balanced with respect to the dc terminals. This leads to very small deviations of the neutral point from the mid-point of the DC source, in spite of the possibly large neutral current. Simulation of inverter circuit, neutral-point and H infinity (H∞ ) has been performed using MATLAB/SIMULINK software. The simulation results confirm the validity of the proposed method